2012 34th International Conference on Software Engineering (ICSE) 2012
DOI: 10.1109/icse.2012.6227018
|View full text |Cite
|
Sign up to set email alerts
|

Improving PSP education by pairing: An empirical study

Abstract: Handling large-sized classes and maintaining students' involvement are two of the major challenges in Personal Software Process (PSP) education in universities. In order to tackle these two challenges, we adapted and incorporated some typical practices of Pair Programming (PP) into the PSP class at summer school in Software Institute of Nanjing University in 2010, and received positive results, such as higher students' involvement and conformity of process discipline, as well as (half) workload reduction in ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 20 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…There is no limitation of computer language or software process model. It can be implemented in pair programming [13] and M-V-C frameworks [14]. Researchers reported that PSP can improve the personal performance of students in both solo and team programming styles.…”
Section: Personal Software Processmentioning
confidence: 99%
“…There is no limitation of computer language or software process model. It can be implemented in pair programming [13] and M-V-C frameworks [14]. Researchers reported that PSP can improve the personal performance of students in both solo and team programming styles.…”
Section: Personal Software Processmentioning
confidence: 99%